Cognitive Research: Principles and Implications - Creem-Regehr, Sarah; Wolfe, Jeremy M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Cognitive Research: Principles and Implications publishes new empirical and theoretical work covering all areas of Cognition, with a special emphasis on use-inspired basic research: fundamental research that grows from hypotheses about real-world problems. We expect that authors will be able to explain in a Significance section how their basic research serves to advance our understanding of the cognitive aspects of a problem with real-world applications.
Keywords: Cognitive psychology; Psychology, Experimental; Neurosciences; Cognitive Psychology; Experimental Psychology; Neuroscience